Pengaruh Service Quality Terhadap Revisit Intention Dengan Perceived Value Dan Patient Satisfaction Sebagai Faktor Mediasi - Dinda Nafatilana; Dewi Sri Surya Wuisan (Jurnal Manajemen dan Administrasi Rumah Sakit Indonesia (MARSI), 2026)
This study aims to analyze the effect of Service Quality on patient Revisit Intention, with Perceived Value and Patient Satisfaction as mediating variables. The background of this study is based on the importance of understanding the factors that encourage patients to revisit health care facilities. This study uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method as an analysis tool. A sample of 130 respondents was obtained through purposive sampling technique, exceeding the minimum number of 111 respondents determined based on G*Power analysis. Data were collected from patients who had received services and had experience in assessing service quality. The results showed that Service Quality had a positive and significant effect on Perceived Value and Patient Satisfaction. In addition, Perceived Value was also shown to have a significant effect on Revisit Intention. However, Patient Satisfaction and Service Quality did not show a significant direct effect on Revisit Intention. Likewise, the mediation pathway through Perceived Value and Patient Satisfaction was not statistically significant. The conclusion of this study is that patients' intention to revisit is more influenced by the perceived value they receive from the service, rather than solely by the quality of the service or their satisfaction. The practical implications of these results emphasize the importance of strategies to increase patient-perceived value as a priority in managing the quality of health services.